Small Portable Object Technology Based Physical Network Security System - Chhabra, Gurpal Singh (My University, 2009)
With the growing network infrastructure to double the previous year, the hacking has became much easier because each node on the internet is connected to other to another directly or indirectly and the tools for hacking increase at slightly higher speed than the tools to protect the intrusion. In the run of this expansion, the physical security of network is one major concern that requires much more attention than what it has. Use of remote monitoring using wireless sensor for physical security is one major answer to it. This thesis work design and develops one of the way in which Sun Spot can provide Physical security to the network infrastructure.
Keywords: Sensor Network; Physical Security; Sun SPOT